Impact of ESG rating and EU regulatory policies on firm value : An empirical study on influence of ESG Rating and EU disclosure legislation on corporate financial performance and value in Europe - Stenroos, Anton (My University, 2024)
The aim of this thesis to examine the relationship between firm's ESG rating and financial performance in Europe during changes in EU disclosure regulation. Sustainability reporting provides investors, companies and legislators transparency and reliability. Non-financial reporting has experienced vast growth in recent years for voluntary and mandatory reasons. Still, the quality of non-financial reporting has been actively questioned of its impact in creating transparency and contributing to more sustainable business environment. To make reports and sustainability scores more reliable, EU has implemented it's Non-Financial Reporting Directive, among other legislations and sustainability frameworks. NFRD mandates large companies to publish non-financial information and impact they have on society. This thesis aims to fill the gap on impact of mandated reporting and give insight to relationship between ESG rating and financial performance. Empirical part of this thesis examines ESG rating's relationship on accounting-based and market-based financial performance and how Directive 2014/95/EU impacts this relationship in Europe. Empirical work uses different pooled ordinary least squares models and fixed effects models with unbalanced panel data acquired from LSEG database. Sample consists of 1972 companies in 32 different countries during years 2011-2022. Regression models give support to stakeholder and legitimacy theory as results indicate that ESG rating has positive influence on financial performance. Providing support that ESG rating can be a tool for company to reduce information asymmetry and risk. Results also indicate that this effect is enhanced for large companies subject to NFRD after 2018 when first reports were mandated. Various robustness tests are used on the results as well as comparing the impacts on two data subsets that contained differing number of countries that are part of European Union. This thesis examines the role of sustainability legislations and offers evidence of the effects during its first years. It provides insight for companies to invest in sustainability and legislators to create more standardized framework for transparency.

Tämän Pro gradun tavoite on tutkia yrityksen ESG-pisteytyksen ja yrityksen taloudellisen suoriutumisen välistä suhdetta Euroopassa, EU:n raportointimääräysten muutosten aikana. Kestävyysraportointi luo sijoittajille, yrityksille ja lainsäätäjille läpinäkyvyyttä ja luotettavuutta. Muiden kuin taloudellisten tietojen raportointi on kasvanut viime vuosina, sekä vapaaehtoisista että pakollisista syistä. Silti raportoinnin laatua on kyseenalaistettu sen vaikutuksesta läpinäkyvyyden luomiseen ja kestävän liiketoimintaympäristön kehittämiseen. Raportoinnin ja kestävyyspisteytyksen luotettavuuden parantamiseksi EU on asettanut Non-Financial Reporting Directive -direktiivin, sekä muita lainsäädäntöjä ja kestävyyskehyksiä. NFRD velvoittaa suuria yritykset julkaisemaan ei-taloudellisia tietojaan ja omia vaikutuksia yhteiskuntaan. Tämä Pro gradu pyrkii täyttämään aukon pakollisen raportoinnin vaikutuksista ja lisäämään ymmärrystä ESG-luokituksen ja yrityksen arvon välisestä suhteesta. Empiirinen osio tutkii ESG-luokituksen suhdetta tilinpäätösperusteiseen ja markkinaperusteiseen taloudelliseen suorituskykyyn ja sitä, miten Direktiivi 2014/95/EU vaikuttaa tähän suhteeseen Euroopassa. Empiirinen työ käyttää erilaisia yhdistetyn vaikutuksen regressioita ja kiinteän vaikutuksen regressioita epätasapainoisella paneelidatalla, joka on hankittu LSEG-tietokannasta. Otokseen kuuluu 1972 yritystä, 32 eri maasta, vuosilta 2011–2022. Regressiomallit tukevat sidosryhmä- ja legitimiteettiteorioita, tulokset osoittavat, että ESG-pisteytyksellä on positiivinen vaikutus yrityksen taloudelliseen suoriutumiseen. Tulokset viittaavat siihen, että ESG-investoinnit voivat olla yritykselle väline vähentää epäsymmetristä informaatiota ja riskiä. Tulokset osoittavat myös, että tämä vaikutus on voimakkaampi suurilla yrityksillä, jotka ovat NFRD:n alaisia vuoden 2018 jälkeen, jolloin ensimmäiset raportointimääräysten mukaiset raportit julkaistiin. Tulosten robustisuuteen käytetään erilaisia testejä, sekä verrataan vaikutuksia kahdella osittaisotoksella, jotka sisältävät eriävät määrät Euroopan unioniin kuuluvia maita. Tämä Pro gradu tarkastelee kestävyyslainsäädännön roolia, ja tarjoaa tärkeää näyttöä sen vaikutuksista direktiivin ensimmäisinä vuosina. Tulokset lisäävät tärkeää näkemystä yritysten kannustimista investoida kestävyyteen ja luo lainsäätäjille kannustimia luoda standardoidumpi kehys kestävälle yritystoiminnalle.
Keywords: ESG, NFRD, Sustainability, Non-financial reporting.